A 0.9‐V human body communication receiver using a dummy electrode and clock phase inversion scheme. Issue 5 (24th October 2022) - Oh, Kwang‐Il; Kim, Sung‐Eun; Kang, Taewook; Kim, Hyuk; Lim, In‐Gi; Park, Mi‐Jeong; Lee, Jae‐Jin; Park, Hyung‐Il
Abstract: This paper presents a low‐power and lightweight human body communication (HBC) receiver with an embedded dummy electrode for improved signal acquisition. The clock data recovery (CDR) circuit in the receiver operates with a low supply voltage and utilizes a clock phase inversion scheme. The receiver is equipped with a main electrode and dummy electrode that strengthen the capacitive‐coupled signal at the receiver frontend. The receiver CDR circuit exploits a clock inversion scheme to allow 0.9‐V operation while achieving a shorter lock time than at 3.3‐V operation. In experiments, a receiver chip fabricated using 130‐nm complementary metal–oxide–semiconductor technology was demonstrated to successfully receive the transmitted signal when the transmitter and receiver are placed separately on each hand of the user while consuming only 4.98 mW at a 0.9‐V supply voltage.